2022
DOI: 10.1177/03616843221091116
|View full text |Cite
|
Sign up to set email alerts
|

Decolonizing Purity Culture: Gendered Racism and White Idealization in Evangelical Christianity

Abstract: Purity culture is a phenomenon promulgated by evangelical Christianity that teaches strict adherence to sexual abstinence prior to heterosexual marriage. Extant research illuminated the ways these teachings have harmed women by normalizing the oppression of their bodies, restricting sexual agency, teaching a shame response to pleasure, and perpetuating rape culture. Notably, these studies have centered white women’s experiences, and to date, there is a dearth of literature examining how these teachings uniquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These studies also might have been limited by social desirability bias, as individuals may have responded to certain items in a way that they believed to be more socially acceptable than their true beliefs, particularly regarding inflammatory topics such as domestic violence. While our samples were ethnically diverse, research showing that ethnicity influences the impact of purity culture (Natarajan et al, 2022) suggests that further work may be needed to document these nuanced presentations of purity culture. In other words, while the present measure is generalizable to these ethnicities, given the composition of our samples, additional ethnically specific items could supplement use of this measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also might have been limited by social desirability bias, as individuals may have responded to certain items in a way that they believed to be more socially acceptable than their true beliefs, particularly regarding inflammatory topics such as domestic violence. While our samples were ethnically diverse, research showing that ethnicity influences the impact of purity culture (Natarajan et al, 2022) suggests that further work may be needed to document these nuanced presentations of purity culture. In other words, while the present measure is generalizable to these ethnicities, given the composition of our samples, additional ethnically specific items could supplement use of this measure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, purity culture is critiqued as further marginalizing women of color by centralizing white women's experiences. While empirical research on purity culture has typically had disproportionately large sample sizes of white people, Natarajan et al (2022) studied the impact of white evangelical purity culture on women of color. Results demonstrated that some women of color had internalized the idea of a white woman as the "ideal pure woman" and felt ostracized within purity culture due to racist stereotypes, such as women of color being inherently promiscuous or fetishized.…”
mentioning
confidence: 99%
“…This includes teachings on God-ordained differences between men and women, validation for men's "headship" in all institutions, and the subsequent doctrine of submission wherein women take a subservient role to men (Bendroth 1993). Recently, EC subculture and institutions have faced heightened and ongoing cultural critiques regarding racism, homophobia, and sexual abuse (see for example, Natarajan et al 2022;McKinzie and Richards 2022).…”
Section: Population Background: Evangelical Christianitymentioning
confidence: 99%
“…In addition to event‐specific factors (e.g., exposure to contaminants, injury severity, closeness to the perpetrator; Pinciotti, Allen, & Riemann, 2022), feelings of dirtiness after sexual trauma may also result from attitudes about modesty and chastity, sometimes referred to as “purity culture” (Owens et al., 2020). Purity culture is rooted in heteronormative gender roles and often involves an emphasis on virginity, particularly among women; the prohibition of physical affection; the need for modesty; sexual gatekeeping; denial of women's bodily autonomy; and a lack of education on sexual consent (Owens et al., 2020; Natarajan et al., 2022). The emphasis on modesty often conveys the idea that women must dress in a way to protect men from lust and sin, as men are viewed as having less self‐control over sexual desires (Owens et al., 2020).…”
mentioning
confidence: 99%